Journal Closure - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2019)
Journal of Infrastructure & Facility Asset ManagementVolume 1, Issue 2, September 2019    (e) ISSN 2656-8896 (P) ISSN 2656-890X JIFAM, Vol.1, Issue 1, March 2019Preliminary Recognition of River Infrastructure    Mahendra Andiek Maulana, Hitapriya Suprayitno & Ria Asih Aryani SoemitroReflection on Data Error Identification Methods for Field Survey Data on Commuter Train Passenger Travel Behavior    Hitapriya Suprayitno & Ria Asih Aryani SoemitroGradation Analysis of Reclaimed Asphalt Pavement from National Road as Asphalt Concrete Layer    Ari Widayanti, Ria Asih Aryani Soemitro, Januarti J. Ekaputri & Hitapriya SuprayitnoMental Tasks EEG Signal Classification Using Support Vector Machine    Wahyu Caesarendra, Syahara U. Lekson & Muhammad AgungSearching the Appropriate Minimum Sample Size Calculation Method for Commuter Train Passenger Travel Behavior Survey    Anita Susanti, Ria Asih Aryani Soemitro, Hitapriya Suprayitno & Vita Ratnasari